2021
DOI: 10.1007/978-3-030-66788-7_3
|View full text |Cite
|
Sign up to set email alerts
|

Aims of Citizenship Education Across Nordic Countries: Comparing School Principals’ Priorities in Citizenship Education 2009–2016

Abstract: The Nordic welfare state has been associated with certain ideas of citizenship, the highlights of which are equal rights, social mobility, democracy, and participation. To better understand how these ideas are interpreted in the educational system, this chapter compares school principals’ prioritization of the aims of civic and citizenship education in four Nordic countries as they are expressed in IEA’s International Civic and Citizenship Education Study (ICCS). We discuss our findings in relation to the Nord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Apart from its ability to foster educational outcomes, classroom discussion is also cherished because it provides an opportunity for students to engage in deliberative discourse and to practice deliberative skills (Aashamar et al, 2018; Andersson, 2012; Avery et al, 2013; McAvoy & Hess, 2013; McDevitt & Kiousis, 2006; Parker, 2010; Sætra, 2018; Samuelsson, 2016; Samuelsson & Bøyum, 2015; Tammi & Rajala, 2018; Teglbjærg, 2023). Deliberative skills and virtues are not only valued by educational researchers and theorists but are also endorsed in the Social Science curricula of various Nordic and European countries, including those of Sweden, Denmark, Germany (Berlin-Brandenburg; e.g., Christensen, 2015), Norway, Finland (Seland et al, 2021), Britain (Peterson, 2009), and France (Audigier, 2002). Though it is worth emphasizing that classroom discussion does not by itself engender deliberation and might even turn into a display of social dominance, discussion constitutes a necessary (yet insufficient) condition for the emergence of deliberative forms of classroom discourse.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from its ability to foster educational outcomes, classroom discussion is also cherished because it provides an opportunity for students to engage in deliberative discourse and to practice deliberative skills (Aashamar et al, 2018; Andersson, 2012; Avery et al, 2013; McAvoy & Hess, 2013; McDevitt & Kiousis, 2006; Parker, 2010; Sætra, 2018; Samuelsson, 2016; Samuelsson & Bøyum, 2015; Tammi & Rajala, 2018; Teglbjærg, 2023). Deliberative skills and virtues are not only valued by educational researchers and theorists but are also endorsed in the Social Science curricula of various Nordic and European countries, including those of Sweden, Denmark, Germany (Berlin-Brandenburg; e.g., Christensen, 2015), Norway, Finland (Seland et al, 2021), Britain (Peterson, 2009), and France (Audigier, 2002). Though it is worth emphasizing that classroom discussion does not by itself engender deliberation and might even turn into a display of social dominance, discussion constitutes a necessary (yet insufficient) condition for the emergence of deliberative forms of classroom discourse.…”
Section: Introductionmentioning
confidence: 99%
“…One such factor is the school management’s support for teachers who wish to engage their students in discussion (Hess & McAvoy, 2015, p. 209). Though the support of school principals potentially promotes classroom discussion, research has shown that Nordic school principals tend to prioritize aspects of social science education that do not necessarily require students to engage in classroom discussions, such as critical thinking and the acquisition of knowledge about social, political, and civic institutions (Seland et al, 2021). In the US context, another changeable school factor is the absence of school-level tracking practices (Hess, 2009, p. 164).…”
Section: Introductionmentioning
confidence: 99%